(untitled) (Heritage, 2023)
The territory of Eastern Serbia throughout history was known for the presence of the Vlach population. The Vlachs came to northeastern Serbia from different regions and were divided into two groups: the Ungrujans and the Carans. The Ungrujans came from the area of Hungary (Transylvania and Banat), while the Carans came from Wallachia and Moldavia. These two groups were not homogeneous, they mixed with each other as well as with the local Serbian population. Nevertheless, during the 20th century and until today, the Vlachs kept their culture and customs, which are significantly different from the Serbian ones. Eastern Serbia is known for Vlach customs, which are inevitably connected with the use of magic, which was an inseparable part of Vlach culture, as well as folk medicine in these regions. Each place had its own sorcerer or sorceress to whom the local population turned for help. Not everyone could be a sorcerer, but this ability was passed down from generation to generation. The Vlachs have always had a rich and interesting mythology, a set of beings, deities, and demons to whom they turned when needed for help. A special place in Vlach magic was occupied by the cult of the Great Mother - Muma Paduri, who was the protector of women. The Vlachs also believe in the power of certain animals and plants that have magical effects. Rituals in Vlach culture were mostly performed in public places, at crossroads, next to rivers and roads. Ritual sites were generally considered off-limits to men, and many rituals are still performed that way today